The Relation between the Raw Milk and Barn Hygiene in Tied Dairy Cows - Silvana Popescu; Eva Andrea Diugan; Cristina El Mahdy; Daniela Oros; Radu Giupana; Cristin Borda (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to investigate the relation between the hygiene of the barns and of the raw milk in tie stall dairy barns. Ten dairy farms with tie stalls from Transylvania were included in the study. The barn hygiene was evaluated based on the cows’ body hygiene. 820 dairy cows were assessed. The hygiene of the raw milk was investigated by the determination of the total bacteria count, in 359 individually milked samples. The data were analysed using the SPSS statistical software. The highest percentage of the 3 and 4 hygiene scores was recorded in the udder area, followed by the upper leg and flank and the lower leg. The total bacterial counts varied greatly in the milk from the investigated farms, from 100 CFU/ml to 307 x 103 CFU/ml. Four of the ten assessed barns were considered dirty and in five barns the total bacterial count exceeded the admitted limit. The barn hygiene correlated significantly with the hygiene of the raw milk (r = 0.82, P = 0.004). The results of the study attested that the hygiene quality of raw milk depends largely on the cleanliness of the barn where the animals are housed.